Study on Behaviour of Self-Healing Concrete Using Silica gel - Sumitha, V; T. Ravichandran, P; Krishnan K, Divya (International Journal of Engineering and Technology, 2018)
The procedures to enhance the strength and reliability of materials depend on the worldview of damage prevention, i.e. the materials are composed and arranged so that the development and expansion of damage is postponed however much as could reasonably be expected. The reinforced concrete structures are subjected to various loads such as heavy vehicles movement, earthquakes, and strong winds etc. which inevitably develop micro cracks. When micro cracks originates, a sequence of events begin within structures. These cracks affect the performance and strength of the structure, in addition withdurability of the structure.To overcome the above problems, it is required to consider the use the Self-Healing Concrete (SHC). In this work the attempt is made to study the use of silica gel as self-healing agent in M60 grade of concrete. The healing agent is mixed in varying proportions are 0.1%, 0.2%, 0.3% and 0.4% respectively by weight of cement inblended concrete mix grade of M60. The performance of silica gel as a self-healing agent was analyzed at different curing periods of 7, 14 and 28days. The concrete specimens were prepared to study the mechanical strength properties lie compressive strength, split tensile strength and flexural strength of blended concrete with and with addition of silica gel.The compressive strength of the blended cement concrete with addition of 0.3 % of silica gel gives 6.54% more strength compare to the control specimens at the age of 28 days testing. The performance of the 0.3% of Silica gel replacement in mechanical strength properties gives considerable effective enhancer compare to the control specimens. Based on the results it can be concluded that the optimum replacement is 0.3% silica gel. Silica gel can be used as one of the healing material in the construction of tunnel, underwater structures etc..Â Â